The Index of Race-Related Stress-Brief: Further Validation, Cross-Validation, and Item Response Theory-Based Evidence. (September 2020) - Chapman-Hilliard, Collette; Abdullah, Tahirah; Denton, Ellen-ge; Holman, Andrea; Awad, Germine
The Index of Race-Related Stress-Brief (IRRS-B) is one of the most widely used measures to assess race-related stress among Black Americans. Despite a long history of use in research and clinical settings, there has been limited scholarship examining the factor structure of the IRRS-B. In this study, we evaluated the item functioning and structural performance of the IRRS-B scores in a nationally recruited sample of Black Americans using item response and confirmatory factor analyses. Item-level analyses illustrated that items on the IRRS-B, in general, tended to be most informative at moderate levels of the latent construct. The proposed three-factor structure yielded a comparable fit to the data in a validation and a cross-validation subsample but did not meet recommended cutoff values for adequate model fit. Findings are discussed in terms of the implications for future use of the IRRS-B in research and clinical contexts.